Does prenatal exposure to antidepressants cause autism? - literature review - Zuzanna Marczyńska; Patrycja Grabowska; Natalia Olesińska; Patrycja Bolla; Hanna Senat; Aleksandra Senat; Aleksandra Madej (Kazimierz Wielki University, 2024)
Autism spectrum disorder is an increasingly diagnosed disorder among children, yet its pathogenesis is still unknown. Possible causes are sought in genetic mutations, cellular processes occurring in the nervous system during development and external factors affecting the fetus during the prenatal period. In recent years, there have been an increasing number of reports linking the occurrence of the spectrum to antidepressant medications, especially from the SSRI group, taken by pregnant women for depressive disorders, which occur in up to a dozen percent of women in this group. The involvement of serotonin in the development of the nervous system during the fetal period is taken as the reason for this phenomenon. To date, no clear consensus has been reached on this issue, and many distractors in the research are highlighted, such as the effect of maternal depression on fetal development, among others. There is no doubt that further research is needed to better assess the risk of ASD associated with SSRI use and dosage during pregnancy